2012
DOI: 10.1371/journal.pone.0032431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Influenza and SIV Specific CD8 T Cell Responses in Macaques

Abstract: Macaques are a potentially useful non-human primate model to compare memory T-cell immunity to acute virus pathogens such as influenza virus and effector T-cell responses to chronic viral pathogens such as SIV. However, immunological reagents to study influenza CD8+ T-cell responses in the macaque model are limited. We recently developed an influenza-SIV vaccination model of pigtail macaques (Macaca nemestrina) and used this to study both influenza-specific and SIV-specific CD8+ T-cells in 39 pigtail macaques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 62 publications
(91 reference statements)
2
19
0
Order By: Relevance
“…Because most human adults have Abs to one or more strains of influenza virus following natural infection, we used plasma from four pigtail influenza-naive macaques (M. nemestrina) as negative controls. We recently showed that 3-to 5-y-old pigtail macaques are seronegative to influenza but seroconvert following experimental infection with influenza (25). As expected, plasma from naive macaques did not contain Abs capable of binding the X-31 HA protein (median OD of 0.0885, significantly less than median OD 1.5745 of the human subjects, p = 0.005; Fig.…”
Section: Influenza-exposed Individuals Possess Nonneutralizing X-31 Vsupporting
confidence: 64%
See 1 more Smart Citation
“…Because most human adults have Abs to one or more strains of influenza virus following natural infection, we used plasma from four pigtail influenza-naive macaques (M. nemestrina) as negative controls. We recently showed that 3-to 5-y-old pigtail macaques are seronegative to influenza but seroconvert following experimental infection with influenza (25). As expected, plasma from naive macaques did not contain Abs capable of binding the X-31 HA protein (median OD of 0.0885, significantly less than median OD 1.5745 of the human subjects, p = 0.005; Fig.…”
Section: Influenza-exposed Individuals Possess Nonneutralizing X-31 Vsupporting
confidence: 64%
“…Three of the macaques studied were subsequently infected with PR8 [A/Puerto Rico/8/1934 (H1N1)], followed by X-31 [A/Aichi/2/1968 (H3N2)] influenza viruses 4 wk apart (10 8 PFU via the respiratory tract). All three macaques became infected with both influenza viruses, as assessed by recovery of influenza RNA from respiratory tract samples and seroconversion, as previously described (25).…”
Section: Subjectsmentioning
confidence: 99%
“…Prior to any procedure, animals were anesthetized intramuscularly with ketamine or ketamine-medetomidine. Animals were inoculated with a total of 9 ϫ 10 6 PFU of virus via the trachea, tonsils, and conjunctivae as described previously (17,42,45). Virus titers in nasal and tracheal secretions and bronchoalveolar lavage (BAL) fluid were determined using standard plaque assays.…”
Section: Methodsmentioning
confidence: 99%
“…Although murine models have been valuable for dissecting NAb and T cell immunity, the ability of influenza virus to induce ADCC in mice remains relatively undefined. The macaque model of influenza virus infection has recently gained popularity, as most human strains of influenza virus readily infect macaques, a large number of nonhuman primate reagents are being established, and macaques show similar pathology and immune responses to influenza virus to those seen in humans (17,(40)(41)(42). Therefore, the use of the macaque influenza model allowed us to dissect the induction and protective capacity of influenza virus-specific ADCC.…”
mentioning
confidence: 99%
“…To identify that CD8 T cells specific for particular Mamu-B017 epitopes could be recovered from Mane-B017 macaques and identified using Mamu-B*017:01 tetramers, frozen PBMCs were thawed and washed in RPMI (Life Technologies, USA) supplemented with 10% fetal calf serum (DKSH, Australia) and expanded as previously described (38). Briefly, PBMCs were split into stimulators and responders at a 1:2 ratio.…”
Section: Methodsmentioning
confidence: 99%